PERCOBAAN PEMBUNUHAN SEBAGAI PENGHALANG KEWARISAN - Fauzan, Fauzan (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2010)
A slaying is seen as one of criminal acts, this was argued by some Mujtahid or some experts in Muslim law who give an independent interpretation of the Koran and Hadits. This was aimed to kill somebodyâ€™s soul. As the implication, this case will make appear a big disadvantage. Moreover, Mujtahid agreed that a slaying was regarded as a criminal act which has an implication towards the case of an inheritance, where the murderer was being hindered to receive the inheritance from his victim. An attempt for slaying which is written in the KHI section 173 letters â€œaâ€, from this we could see the extension of the meaning slaying as a reason to hamper an inheritance.